Spatio-temporal links between urban sprawl and natural protected areas. A case study on Valparaiso region, Chile. - Felipe Jorquera Guajardo; Alejandro Salazar Burrows; Claudia Montoya-Tangarife (Investigaciones Geográficas, 2017)
Peri-urbanization in urban areas is the creation of a rural-urban belt that produces multiple land use changes, relocation of economic activities, and new transport and communications settings. These transformations in the Valparaíso region reveal themselves through changes in space occupation, outlining an internally connected and accessible space with multifunctional outskirts filled with new activities and inhabitants, coexisting with protected wild areas or Natural Protected Areas (NPA), which are considered alluring for peri-urbanization processes. This article characterizes the evolution of peri-urbanization processes and analyzes spatial changes related to NPA in the Valparaíso region, for the 2003-2015 period. Land use typologies were established, and the main spatio-temporal transformations were determined, while connecting them with the intensity of the urban expansion over the NPA. Results show the pressure of the peri-urban expansion on the NPA in the region over the last years, which has drastically increased the appearance of new residential spaces; a clear example of this is the scattering of country houses throughout the region during the period studied. Particularly, the NPA that are not a part of the State’s Protected National System of Wildlands showed bigger transformations. Protection over these areas, which are a part of Valparaíso’s identity, has been put at risk as a consequence of the constant urban sprawl in the region.